1999
DOI: 10.1046/j.1365-2567.1999.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microscopy of murine islets of Langerhans: increased adhesion of transferred lymphocytes to islets depends on macrophage‐derived cytokines in a model of organ‐specific insulitis

Abstract: Environmental factors contribute to the pathogenesis of type 1 diabetes (insulin-dependent diabetes mellitus). Multiple low doses of streptozotocin (MLDS) induce hyperglycaemia and insulitis in mice. Previously we demonstrated that adhesion of lymphocytes to endothelium of islets is only increased when donor animals were diabetic and recipient mice had received 5 mg/kg streptozotocin (STZ). Therefore we used streptozotocin to evaluate the immunological relevance of such an irritation of islets. Lymphocytes, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Interactions of lymphocyte function-associated antigen 1 (LFA-1) with ICAM-1 during priming induce both qualitative and quantitative alterations in T effector function and induce potentially autodestructive responses [37]. In experimentally produced diabetes the expression of adhesion molecules was lower than that of healthy controls [38]. These results are in accordance with those of Spatz et al who reported that human APC-s express lower levels of ICAM-1 [14].…”
Section: Discussionsupporting
confidence: 77%
“…Interactions of lymphocyte function-associated antigen 1 (LFA-1) with ICAM-1 during priming induce both qualitative and quantitative alterations in T effector function and induce potentially autodestructive responses [37]. In experimentally produced diabetes the expression of adhesion molecules was lower than that of healthy controls [38]. These results are in accordance with those of Spatz et al who reported that human APC-s express lower levels of ICAM-1 [14].…”
Section: Discussionsupporting
confidence: 77%
“…28 Furthermore, lymphocyte adhesion and infiltration decreased upon silica-mediated depletion of the Mf additionally suggesting that the Mf were also involved in the recruitment of lymphocytes. 29,30 This process is not only specific for pancreas, the loss of marginal zone Mf as the result of chronic Leishmania infection severely abrogated normal trafficking of lymphocytes into the white pulp of the spleen. 31 DC and Mf possibly act by inducing the addressins VCAM-1, MAdCAM-1 and ICAM-1 on the pancreatic endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…4a). These changes in rolling behavior were not caused by alterations in blood flow which remained constant throughout the experiment as determined by a semi‐quantitative score (data not shown (30). Injection of an intracutaneous depot of sodium chloride did not induce enhanced rolling of T cells.…”
Section: Resultsmentioning
confidence: 85%